Occupancy-based Energy Management System in Campus Building: A Case Study in Electrical Engineering Department Building, ITN Malang - Sulistiawati, Irrine Budi; Soetedjo, Aryuanto; Zulfani , Dyah Erika Mining Aurora; Muljanto, Widodo Pudji; Susanti, Debby Budi; Sukowiyono, Gaguk (Program Studi Teknik Elektro S1 ITN Malang, 2024)
Building energy management systems provide an effective method for energy saving. An occupancy-based energy management system considers the occupants' behavior that affects energy consumption. This paper presents the investigation of different scenarios based on the occupancy to control the energy consumption in the Electrical Engineering Department Building, ITN Malang. The results show that switching off the appliances when the occupants go home in the afternoon reduces the monthly energy consumption by 33.95%. The result indicates that the occupants' awareness regarding energy saving has recently been low. Thus, the occupancy sensor and automatic time scheduling for the appliance control are suggested to be installed.